Einstein Snake and Ladder Game: A Game-Based Physics Learning Media for Interactive and Enjoyable Classrooms - Lalu Azikri Amrullah; Nanda Sulistia Wardani; Elgarisna Rambunewa; Ahmad Harjono; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2024)
This article discusses innovations in physics learning methods through the use of game-based media, specifically a snakes and ladders game designed with educational elements. In the context of an ever-evolving educational landscape, traditional approaches are often considered less effective in capturing student interest, particularly in complex subjects like physics. Therefore, this research developed a media tool called "Einstein's Snake and Ladder Game" as an innovative solution to enhance student motivation, engagement, and understanding of physics concepts. Using a mixed-methods research approach, this article explains the media creation process from the preparation stage to production as well as its relevance to physics education. The design tools utilized included Canva and Microsoft Word, while media validation was measured via Google Forms. The results indicate that this game not only helps students grasp the material more effectively but also fosters a more inclusive and enjoyable learning environment. Consequently, this game-based media is expected to address challenges in physics education and make the learning process more engaging for students.